EVOLUTION AND PROSPECTIVE VECTORS OF MARKETING INNOVATIONS DEVELOPMENT IN RETAIL - VASYLCHENKO, Lidiia; AKHTOIAN, Arman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the evolution of marketing innovations in the retail sector through the lens of technological development and the transformation of consumer expectations. Five key stages of innovation development are identified—traditional, network based, digital, omnichannel, and innovation-technological—each characterized by specific challenges, opportunities, and influencing factors. The traditional stage was marked by a focus on product policy and individual promotions within the physical store. The network-based stage introduced the integration of IT solutions into logistics, CRM systems, and initial customer segmentation. The digital stage was distinguished by the emergence of online stores, mobile marketing, and personalized communication. The omnichannel stage involved the full synchronization of online and offline channels to ensure a holistic customer experience. The innovation-technological stage includes the extensive implementation of artificial intelligence, AR/VR, blockchain, and emotional analytics. The study draws conclusions about the patterns of transition between stages and the role of innovation in transforming business models in retail. Key directions for further development of marketing innovations are identified, including the technologization of customer experience, intelligent marketing automation, a sustainable approach, Web3 integration, the growth of social commerce, and the use of emotional analytics. However, the implementation of these directions is accompanied by a number of challenges related to the rapid pace of technological change, increasing consumer expectations, and the need to adapt business models to new ethical and environmental standards. In Ukraine, these challenges are further intensified by martial law conditions, market instability, limited resources, and the urgent need for rapid transformation of the retail sector to fit the new realities. It is noted that the development vectors of marketing innovations in retail form a complex yet high-potential system of change that requires strategic thinking, flexibility, and readiness to implement new formats of customer interaction. The article has practical significance for marketing professionals, retail business managers, and researchers working on adapting business practices to the evolving digital economy.
Keywords: retail; marketing innovations; omnichannel; customer experience; digital technologies